Method of multiple scales on Duffing oscillator equation and the existence of its limit cycle - Putra, Gusrian; Supmawati, Meysi; Prasetyo, Bayu (Transcendent Journal of Mathematics and Applications, 2023)
The Duffing Oscillator equation is a second-order nonlinear differential equation that describes an oscillator with a cubic nonlinearity. In this paper, the Duffing equation involves damping factors, restoring forces, periodic force and its frequency, and nonlinearity constants. One of the perturbation techniques that can be used to determine the approximate solution of the Duffing oscillator equation is the method of Multiple Scales. Due to the existence of a sinusoidal periodic force in the equation, the Multiple Scales method produces a sinusoidal approximation as its solution. The solutions are also in a good agreement with the numerical results for small nonlinearity constants. The smaller the nonlinearity constant, the smaller the error obtained with the numerical results in comparison. The approximate solution also tends to be sinusoidal for small nonlinearity constants. Finally, the approximate solution obtained is able to predict the existence of a limit cycle in the Duffing Oscillator equation around the origin due to the existence of its particular solutions.